2022
DOI: 10.1038/s41467-022-32926-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cross-neutralizing antibody that targets the receptor binding site of H1N1 and H5N1 influenza viruses

Abstract: Influenza A viruses pose a significant threat globally each year, underscoring the need for a vaccine- or antiviral-based broad-protection strategy. Here, we describe a chimeric monoclonal antibody, C12H5, that offers neutralization against seasonal and pandemic H1N1 viruses, and cross-protection against some H5N1 viruses. Notably, C12H5 mAb offers broad neutralizing activity against H1N1 and H5N1 viruses by controlling virus entry and egress, and offers protection against H1N1 and H5N1 viral challenge in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…In principle, this mode of binding could allow for a constant usage of the light chain for RBS engagement that is paired with different heavy chains to optimize binding with Ca2. Interestingly, while this manuscript was in revision, a structure of another mouse-derived antibody, 12H5, was reported which shows a similar mode of binding with the head domain of CA/04/09 HA 45 (Fig. 8 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In principle, this mode of binding could allow for a constant usage of the light chain for RBS engagement that is paired with different heavy chains to optimize binding with Ca2. Interestingly, while this manuscript was in revision, a structure of another mouse-derived antibody, 12H5, was reported which shows a similar mode of binding with the head domain of CA/04/09 HA 45 (Fig. 8 ).…”
Section: Discussionmentioning
confidence: 89%
“…Comparing the vaccination strategies utilized reveals contrasting approaches. While 1F8 was generated by a prime-boost regimen with a recombinant P1-expressing virus 11 , 12H5 was discovered after sequential immunization with three separate historical virus strains 45 . This has major implications in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…43 Although GWAS data for infection with other avian IAV subtypes, such as H5N1 and H9N2, are currently unavailable, our findings might be reasonably extrapolated to other avian IAV infections. [44][45][46] Our analysis has focused on total IgA levels rather than subtype-specific antibodies, suggesting that IgA concentration could serve as a useful biomarker for identifying individuals at an increased risk of avian IAV infection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a novel humanized Mab 8A 56 neutralized H5N1 by binding to two types of epitopes on HA. Li et al described a chimeric Mab, termed C12H5, which could neutralize representative strains of H1N1 circulating from 1991 to the present; it could even cross-neutralize H5N1 57 . It has been reported that neutralizing antibodies against HA, isolated from volunteers vaccinated with seasonal influenza vaccines, could protect mice from H1N1 and H3N2 viruses in vivo 58 .…”
Section: Introductionmentioning
confidence: 99%